An Economical Method for Simultaneously Improving Pretreatment and Anaerobic Fermentation Effects on Corn Straw Using Ultra-Low Concentration FeCl2 - Yina Qiao; Xuebin Lu; Zehao Zhi; Shuting Zhang (Energies, 2020)
Low pollution, slight corrosion, and low cost are the main challenges in the conversion of biomass to biogas. In this work, based on the whole process optimization of biomass conversion, an effective method using an ultra-low concentration of FeCl2 was proposed to simultaneously promote the biochemical reaction and improve the pretreatment effect. The concentration of FeCl2 in the pretreatment was determined according to the requirements of the minimum amount which led to the optimal performance of the anaerobic system and had economical importance. The effects of FeCl2 in the pretreatment and anaerobic fermentation were evaluated by comparing with that of distilled water in the production of hydrolysis products and organic acids. The optimal condition was obtained at 180 °C and 10 min with 1 × 10−5 mol/L FeCl2 pretreatment. At that condition, hemicellulose achieved a high conversion of 97.6%, and the released xylose reached nearly 95%. At least 77.5% of the organic matter in the solution can be utilized for subsequent fermentation. FeCl2 pretreatment also accelerated the anaerobic acidification fermentation process and promoted organic acid yields. The work provided a meaningful and economical choice for the conversion technology of biomass to biogas.